THE OPPORTUNITIES TO DEVELOP COMMUNICATION AND COOPERATION SKILLS AT CHILDREN'S COMMUNITY CARE HOMES - Gudzinskiene, Vida; Raudeliunaite, Rita (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2022)
The purpose of the article is to reveal the opportunities to develop communication and cooperation skills in children living at children’s community care homes (further on CCCHs) based on the experience of social workers working at CCCHs. Problematic question: What are real opportunities for children to develop communication and cooperation skills while living at CCCHs? Nine social workers, who work at CCCHs in seven different locations in Lithuania, participated in the research. The study revealed that, while living at CCCHS, the opportunities to develop communication and cooperation skills change in the positive direction. At CCCHs, a positive family environment, in which closer and warmer relationships form, is created, more time is devoted to mutual communication. Children develop communication and cooperation skills  while creating home rules, negotiating and obliging themselves to stick to the set order, learning to create and maintain harmonious mutual realtionships, empasising attentiveness, politeness, empathy, as well as learning to resolve problems and conflicts in a constructive manner, conculting and agreeing regarding the ways to spend their leisure time. In addition, children, while expanding their social ties in their community, learn to coexist with others, as well as to develop social resilience while learning to resist the pressure of others, not to  give in to bad influences, to trust their own strength and to take decisions independently.